Variability of outcome measures in trials of intravenous therapy in acute severe paediatric asthma: a systematic review. Issue 4 (27th November 2018) - Gray, Charmaine S; Powell, Colin V E; Babl, Franz E; Dalziel, Stuart R; Craig, Simon
Abstract : Objective: To determine the variability of primary and secondary outcomes used in trials of intravenous bronchodilators in children with acute severe paediatric asthma. Methods: Systematic search of MEDLINE, EMBASE, Cochrane CENTRAL and the WHO International Clinical Trials Registry Platform for randomised trials in children (less than18 years) with acute severe paediatric asthma comparing intravenous bronchodilator therapy to another treatment. Initial search was performed on 7 January 2016 with an updated search performed on 6 September 2018. Primary and secondary outcomes were collated. Results: We identified 35 published papers and four registered study protocols. 56 primary outcomes were found, the most common being a clinical asthma score (23/56; 41%). Other identified primary outcomes included bedside tests of respiratory function (11/56; 20%) and measures of length of stay (9/56; 16%). There were a total of 60 different secondary outcomes, the most common were various length of stay measures (24/60; 40%) and adverse events (11/60; 18%). Conclusion: Studies comparing intravenous treatment modalities for children with acute severe paediatric asthma exhibit great variation in the type, number and timing of outcome measures used. There are no patient or family-specific outcomes reported. There is a need to develop international consensus. Trial registration number: CRD42017055331.